Peripheral ossifying fibroma - Sarmiento, Melchor A.; Militante, Jose AG.; Maglutac Mariano T.
Peripheral ossifying fibroma is a reactive hyperplastic gingival lesion that is believed to be derived from connective tissue of the submucosa and periodontal ligament. It has predilection for young remales, and occur mostly in the gingiva anterior to the molars. The aim of this paper is to present a case a 20-year old female patient who was referred to the Oral Surgery Section of the Emilio Aguinaldo College, School of Dentistry for diagnosis and management of a gingival mass on the left mandibular area. The lesion was removed under local anesthesia and sent to the pathology laboratory for histopathologic examination. Result revealed that it was peripheral ossifying fibroma. A brief review of current literature is also presented.
Keywords: Peripheral ossifying fibroma; Periperhal fibroma; Peripheral cemento-ossifying fibroma; Peripheral cementifying fibroma